Shear Strength Degradation Behavior of Offshore Clay Under Cyclic Loading - Thian S.Y.; Lee C.Y. (Springer New York LLC, 2023)
Geotechnical engineering; Ocean engineering; Cyclic degradations; Cyclic shear strain; Cyclic stress amplitudes; Deformation Characteristics; Direct simple shears; Over consolidation ratio; Pore-water pressures; Strength degradation; Shear strain; amplitude; clay; consolidation; cyclic loading; deformation; degradation; shear strain; shear strength; soil mechanics